226k views
1 vote
I do not understand how to figure this out.....

2(3x+6)=42

2 Answers

3 votes

Answer:

The answer would be x=5

Explanation:

2(3x+6)=42

so what you're gonna do is use the distributive property, so you would multiply 2 and 3x, and 2 and 6. so then you would have:

6x+12=42

Now you want to get rid of the twelve so you can solve for x. So you are going to subtract 12 from 12 and 42. So now you have:

6x=30

Next you're going to divide 6x and 30 by 6. So you would have x=5

User Aedvald Tseh
by
5.7k points
5 votes

Answer:

5

Explanation:

2(3x + 6) = 42

(3x + 6) = 42/2

(3x + 6) = 21

3x + 6 = 21

3x = 21 - 6

3x = 15

x = 1/3

x = 5

User Tlvs
by
5.0k points